Direito aos medicamentos seguros, eficazes e de qualidade: interações entre os sistemas do direito, da saúde e da economia a partir da teoria dos sistemas sociais de Niklas Luhmann - Kölling, Gabrielle Jacobi (Universidade do Vale do Rio dos Sinos, 2018)
The present work refers to the research of doctorate that fits in the subject of the right to the health and to the medicines insurance, effective and of quality. The right to health is involved in a highly complex, contingent, paradoxical and risky environment. These characterizations of legal expectation related to health are not exclusive to this fundamental right: they also mark the characterization of contemporary society and law as a whole. In order to analyze the right to health, it is necessary to observe its limits and its relationship with the medical system, as well as the discussion arising from these contours in the theory of social systems. Within these systems, we have the drugs and all of their burden of complexity in relation to tripod safety, quality and effectiveness. The "old dogmatic" of law is not capable of responding to the characteristics of current juridical and social phenomena; In this sense, the problem of traditional sources of law and its need for horizontalization within the fertile ground of "normative production" of the National Agency of Sanitary Surveillance (ANVISA) when it comes to "drug regulation" is evident, as well as the dialogue with the economic system. At present, there are innumerable possibilities regarding medicines, among which falsification can be considered an alternative or possibility, especially in contexts of social inequities. Exacerbated poverty and price are factors in the low accessibility of safe, effective and quality medicines. Thus, the aim of this thesis is to analyze the right to health in the context of safe, effective and quality medicines and their correlations with the system of economy and law, in the regulatory bias. For that, the theoretical-methodological framework will be Niklas Luhmann's Theory of Social Systems. Finally, it is observed that in Brazil the regulation and intervention in the medicine market is still incipient and deficient; countries with a context of "deregulation" of drug prices are more successful in accessibility, however, these same countries do not present accentuated social inequities as in Brazil.
Keywords: Sistema médico; Sistema da saúde; Fármaco; Falsificação; Preço; Acessibilidade; Medical system; Health system; Drug; Falsification; Price; Accessibility; ACCNPQ::Ciências Sociais Aplicadas::Direito